The Discrete Heal Algorithm With Intermediate Goods - Cremer, Jacques (Review of Economic Studies, 1983)
Journal Article The Discrete Heal Algorithm With Intermediate Goods Get access Jacques Cremer Jacques Cremer University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 50, Issue 2, April 1983, Pages 383–391, https://doi.org/10.2307/2297424 Published: 01 April 1983 Article history Received: 01 October 1981 Accepted: 01 October 1982 Published: 01 April 1983